2017
DOI: 10.1007/s11657-017-0352-1
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the public health impact of vitamin D-fortified dairy products for fracture prevention

Abstract: PurposeDairy products are rich in nutrients that positively influence bone health and hence fracture risk, and have therefore been recommended and used for fracture prevention. To help decision makers to efficiently allocate scare resources, it is further important to assess the public health and economic impact of any health intervention. In recent years, several studies have been conducted to estimate the public health and/or economic impact of dairy products but no overview is currently available. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…The potential bias by the corporate funding of trials or even speaker fees or travel grants should not be neglected [ 141 , 142 , 143 ]. Of 22 review articles (in English, found in PubMed by the search term “review AND (milk OR dairy) AND (osteoporosis OR fracture)” and limited to those papers with milk, dairy, or other dairy products in the titles published in 2016–2020) published in the past years, 13 papers [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ] were written by at least one author with links to the dairy industry or dairy associations, whereas the authors of nine papers [ 4 , 9 , 10 , 157 , 158 , 159 , 160 , 161 , 162 ] did not report any such conflicts of interest. Although not explored, the proportion of opinion papers, comments, and letters to the editors with conflicts of interest is likely to be higher.…”
Section: Author Autonomy From Dairy Industrymentioning
confidence: 99%
“…The potential bias by the corporate funding of trials or even speaker fees or travel grants should not be neglected [ 141 , 142 , 143 ]. Of 22 review articles (in English, found in PubMed by the search term “review AND (milk OR dairy) AND (osteoporosis OR fracture)” and limited to those papers with milk, dairy, or other dairy products in the titles published in 2016–2020) published in the past years, 13 papers [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ] were written by at least one author with links to the dairy industry or dairy associations, whereas the authors of nine papers [ 4 , 9 , 10 , 157 , 158 , 159 , 160 , 161 , 162 ] did not report any such conflicts of interest. Although not explored, the proportion of opinion papers, comments, and letters to the editors with conflicts of interest is likely to be higher.…”
Section: Author Autonomy From Dairy Industrymentioning
confidence: 99%
“…The advantages of dietary interventions are that they are largely free of adverse effects (food intolerance excepted) and cost-effective for both consumers [19,20] and the public health system in countries where supplements are funded. They may also be preferred by women who favour "natural" interventions and whose taste preferences align with such diets.…”
Section: Dietmentioning
confidence: 99%
“…Using these cost distributions and obtaining annual costs for 20 μg (800 IU) vitamin D per day of 0.11 Euros per person and annual costs for 200 mg calcium per day of 0.22 Euros per person it was estimated by Sandmann et al that the implementation of a vitamin D plus calcium fortification programme in Germany would cost 41 million Euros per year while saving 365 million Euros per year as a result of reduced fracture costs ( 139 ). This would translate into a benefit-cost ratio of 9:1 which is even more conservative than other estimates of the cost-effectiveness of pure vitamin D interventions with even higher benefit-cost ratios ( 138 , 140 149 ). We are well aware that more data are needed on the cost-effectiveness of systematic vitamin D fortification but we conclude that, despite limited evidence, the available literature suggests that this approach is highly likely to be cost-effective.…”
Section: Cost-effectiveness Of Vitamin D Food Fortificationmentioning
confidence: 86%